Poverty and well-being in Mozambique: the second national assessment - National Directorate of Planning and Budget; Ministry of Planning and Finance; Economic Research Bureau; International Food Policy Research Institute; Purdue University (National Directorate of Planning and Budget, 2004)
This report has very focused objectives. It seeks to present the methodology and results of the poverty analysis of the 2002-03 IAF as well as comparisons with the 1996-97 survey results. The results point to a substantially improved poverty picture relative to 1996-97. The national poverty headcount, defined as the share of the population living in poverty, declines to 54 percent, a 15 percentage point decline from the levels registered in 1996-97. Poverty reductions are more rapid in rural than in urban zones, narrowing considerably the differences in poverty between the two zones, though poverty levels remain higher in rural compared with urban zones. Larger than average reductions in poverty are registered in Niassa, Zambézia, Nampula, Tete, Manica, and Sofala.